The Hybrid Nature of Volunteering: Exploring Its Voluntary Exchange Nature at Music Festivals. (December 2016) - Toraldo, Maria Laura; Contu, Alessia; Mangia, Gianluigi
This article discusses the nature of volunteering by exploring the features of the exchanges involved and their precise meanings. The context for this analysis is the U.K. music festival industry, where volunteers are offered specific "exchange deals" for providing their work efforts. The article argues that it is in such exchanges, and in their inherent meanings, that the nature of volunteering can be appreciated as a complex and multi-dimensional phenomenon. By theorizing volunteering as possessing Janus-face features represented by its symbolic and economic faces, this research demonstrates that the practice of volunteering is inherently hybrid. This article advances conceptual knowledge on volunteering by showing the irreducibility of the concept to either of these symbolic or economic dimensions. It offers a new perspective that addresses apparently incompatible readings of volunteering, recognizing volunteers' different experiences and how they feel about the nature of their exchange.